Synthesizing Speech with Selected Perceptual Voice Qualities – A Case Study with Creaky Voice - Rautenberg, Frederik; Seebauer, Fritz; Wiechmann, Jana; Kuhlmann, Michael; Wagner, Petra; Haeb-Umbach, Reinhold (Interspeech 2025)

Bryant, Jonathan: Compassion and the Characterization of the Markan Jesus (Biblical Interpretation Series, Band: 223) - Breuer, Saskia Rebecca (ThRv)

Du hast es Dir verdient.“ Ökonomische Perspektiven auf den (selbstgestalteten) Tod im Roman Die Königin der Berge (2018) und das digitale „Leben nach dem Tod“ in der Serie Upload (seit 2020) - Harmening, Anda-Lisa (The (Un)Speakability of Death. Contemporary Literarisations and Visualisations of Dying)

Vol. 4 No. 1 (2025): The (Un)Speakability of Death. Contemporary Literarisations and Visualisations of Dying (Re:visit Humanities & Medicine in Dialogue)

Test-oriented Resilient Requirements Engineering (ToRRE): extending model-based effect chain analysis to verification objectives - Gräßler, Iris; Ebel, Marcel (Proceedings of the Design Society)
Verification and Validation (V&V) are essential processes in engineering Cyber-Physical Systems. However, the role of V&V engineers is often not given sufficient attention. Based on a systematic literature analysis and practical observations, a four-step method for Test-oriented Resilient Requirements Engineering (ToRRE) is developed. The steps are planning V&V, executing V&V activities, documenting V&V activities and analyzing results of V&V activities. Applying ToRRE ensures continuous information flow and traceability. Engineers are enabled to analyze requirements using engineering artifacts connected through Model-Based Systems Engineering. Adopting methods for Model-Based Effect Chain analysis to evaluated test cases and test scenarios, conclusions on requirements engineering and change management are enabled. The method is evaluated in an EU research project.
Keywords: systems engineering (SE); product modelling/models; design methods; verification & validation; test cases & test scenarios

Sex-differences in autonomic and cardiovascular responses to multimodal therapy in Parkinson’s disease: a pilot study - Siche-Pantel, Franziska; Mühlenberg, Manfred; Buschfort, Rüdiger; Michels, Heinke; Jakobsmeyer, Rasmus; Oesterschlink, Julian; Reinsberger, Claus (BMC Neurology)
Abstract Background Parkinson’s Disease (PD) bears a variety of sex differences and is associated with cardiovascular dysregulation (CDR). Variation in the routinely assessed standard parameters heart rate (HR) and blood pressure (BP) seem not well understood within the frame of sex-specific developments under therapy. Parameters of heart rate variability (RMSSD) and electrodermal activity (meanEDA) may assist the understanding of underlying autonomic developments. This pilot study aims to describe sex-specific cardiovascular and autonomic responses to a multimodal inpatient rehabilitation program in patients with PD. Methods Forty-one PD patients (24 male, 17 female) participated in a stationary, multimodal therapy intervention (MTI). Before and after MTI, HR, BP, RMSSD, and meanEDA were assessed in supine baseline (5 min of rest before orthostasis) and during supine adaption to rest (5 min of rest after orthostasis). Differences between baseline and adaption to rest as well as differences over time of MTI were calculated using Wilcoxon test; sex differences using Mann–Whitney-U test. Results Before MTI, women’s supine HR ( p = .034*; d = .17) and BP ( p = .015*, d = 0.4) were significantly higher during adaption to rest than during baseline. After MTI, women’s supine HR ( p = .020*; d = .84) and BP ( p = .022*, d = 0.5) during adaption to rest had decreased significantly. Men’s HR and BP remained constant and without differences between the supine conditions. RMSSD and meanEDA remained steady in both sexes. Conclusion The sex-specific responsiveness to MTI supports the concept of sex-sensitive therapeutic management for cardiovascular symptoms in PD. In both sexes, peripheral cardiovascular outcomes appeared not attributable to corresponding outcomes in autonomic regulation. Further examination of autonomic parameters could provide a foundation for developing therapeutic approaches that address central nervous system mechanisms. The study was officially registered (08/2020). The data supporting the findings of this study are available under http://apps.who.int/trialsearch/ under trial number DRKS00022773.

Shifting boundaries from preparedness to response: Using simulation of rescue robots in weather-induced emergencies - Gräßler, Iris; Döhner, Niklas; Ebel, Marcel; Pottebaum, Jens (Mensch und Computer 2025 - Workshopband)
In early operational phases of severe weather events, a lack of information challenges emergency management teams to gain an overview of the situation and make informed decisions. To support situational exploration, unmanned aerial and ground vehicles attract increasing attention, primarily used to document operational sites. However, they offer further potential in early operational phases. To ensure their reliable use for exploration, decision-makers must be aware of opportunities and limitations under prevailing conditions. For this, use cases for robotic simulation in emergency response are presented, considering technical restrictions and dynamic influences from weather impacts. The approach of integrating rescue robot simulation into the response phase is developed following a five-step research design. Existing use cases of rescue robot simulation are identified in a systematic literature analysis. The results are extended with use cases developed for urban flooding scenarios. Subsequently, use cases are assessed and selected for implementation in the simulation environment Gazebo. Finally, the results are validated with end users in the EU research project CREXDATA, which focuses on decision support based on processing extreme data. The implemented use cases demonstrate the potential of robotic simulation in emergency response to accelerate action planning in decisionmaking and provide a more detailed picture, enabling betterinformed decisions.
Keywords: robotic simulation; rescue robots; emergency response; extreme weather

Theorising forward: positioning deductive elaboration in the Information Systems research repertoire - Paré, Guy; Wagner, Gerit; Tate, Mary; Schryen, Guido; Templier, Mathieu (European Journal of Information Systems)

Alltagskultur im Vormärz (= FVF Jahrbuch 2024).

„So waren wir“, oder: „Geschichte wiederholt sich nicht, aber sie reimt sich.“ Laudatio zur Verleihung des Margarete-Schrader-Literaturpreises der Universität Paderborn an Martin Becker. - Eke, Norbert (Literatur in Westfalen. Beiträge zur Forschung 21. Im Auftrag der Literaturkommission für Westfalen des Landschaftsverbandes Westfalen-Lippe)

„Die Toten der Zukunft sind / Die nicht wachbleiben / In diesem Traum / Im Heiligen Theater des Jetzt“. Messianische Zeitlichkeit im Theater Werner Fritschs. - Eke, Norbert (Zukünftigkeit im zeitgenössischen Drama und Theater. Literatur- und theaterwissenschaftliche Studien.)

(Prä-)Modernität? Das Ringen um Zeit und Zeitgenossenschaft in der Literatur der Vormärz- und der Revolutionsepoche. - Eke, Norbert (Die Modernität von 1848/49. Ambivalente Aufbrüche und neue Zugänge zur Revolution.)

Erkundungen im destrukturierten Süden. Marlene Streeruwitz‘ literarisches Maskenspiel Die Reise einer jungen Anarchistin in Griechenland (2014). - Eke, Norbert (Deutsche Griechenland-Diskurse und Griechisch-Deutscher Kulturtransfer.)

Unverfügbarkeit – Latenz – Widmung. Das Heilige (in) der Kultur. - Eke, Norbert (Das Heilige (in) der Kultur. Unverfügbarkeit – Latenz – Widmung.)

Epochenzugehörigkeit und Werkentwicklung. - Eke, Norbert (Gotthelf-Handbuch. Leben – Werk – Wirkung.)

Was im Gedicht geschieht. Jan Wagner, Paderborn Wintersemester 2023/24: Die 42. Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller. Zur Einführung. - Eke, Norbert (Was im Gedicht geschieht: Jan Wagner. Paderborn Wintersemester 2023/2. 42. Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller.)

Unschärfen – Ambiguitäten – Mehrdeutigkeiten. Eine ( Jan Wagners) poetologische ‚Klarstellung‘ lyrischer Praxis. - Eke, Norbert (Was im Gedicht geschieht: Jan Wagner. Paderborn Wintersemester 2023/2. 42. Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller.)

Alltagskultur im Vormärz. Vorbemerkung. - Eke, Norbert (Alltagskultur im Vormärz (= FVF Jahrbuch 2024).)

Erste Begegnung. - Eke, Norbert (Literatur in Westfalen. Beiträge zur Forschung 20.)

IBB: Fast Burrows-Wheeler Transform Construction for Length-Diverse DNA Data - Adler, Enno; Böttcher, Stefan; Hartel, Rita; Steininger, Cedric Alexander (23rd International Symposium on Experimental Algorithms)